Effect of different nitrogen levels and biofertilizers on growth, yield and nutrient content of Chrysanthemum - Kumari, Anop; Goyal, R.K.; Choudhary, Mahesh; Sindhu, S.S. (Annals of Agricultural Research, 2014)
A pot experiment was conducted in the screen-house of the Department of Horticulture, College of Agriculture, CCS Haryana Agricultural University, Hisar during 2011-12 and 2012-13 to investigate the effect of different levels of nitrogen (0, 10, 20 and 30 g/m2) and biofertilizers (Azotobacter andAzospirillum) on growth, yield and nutrient content of Chrysanthemum. The interaction effect of different levels of nitrogen and biofertilizers on number of branches per plantwas found to be non-significant during both years of experimentation. The fresh weight of plant was found to be significant during both the years. In the year 2011-12, the maximum fresh weight of plant (102.36 g) was noticed with the application of Azospirillum along with nitrogen 20 g/m2, whereas, in second year, it was maximum (103.45 g) with the application of Azospirillum incombination of nitrogen 30 g/m2. The maximum dry weight of plant (10.52 and 10.50 g) was observed in the application of Azospirillum along with nitrogen 20 g/m2, which was at par with Azospirillum along with nitrogen 30 g/m2 (10.06 and 10.40 g). The maximum flower yield per plant (59.16 and 67.22 g) was recorded with Azospirillum application alongwith nitrogen 20 g/m2. However, in second year, it was at par with Azotobacter in combination of nitrogen 20 g/m2 (61.70 g). In the year 2011-12, the maximum nitrogen content (4.79%) was recorded in Azospirillum along with nitrogen 30 g/m2, whereas, in the next year, it was recorded maximum (4.65%) in Azotobacter along with nitrogen 30 g/m2, which was at par with Azospirillum along with nitrogen 30 g/m2 (4.55 %). Interaction effect of nitrogen and biofertilizers on phosphorus and potassium content were found to be non-significant during both the years of investigation.